Thermal behaviour of bambus[6]uril and its chloride caviplex - Cicolani, Renato Salviato; Job, Aldo Eloizo [UNESP]; Tonin, Fernando Gustavo; Correia, Henrique Dias; Demets, Gregoire Jean-Francois (Springer, 2019)
The present paper presents the thermal behaviour of methyl-bambus[6]uril in its anion-free and chlorine-included form. Our study was based on thermogravimetry associated to Fourier-transform infrared spectroscopy and differential scanning calorimetry. The compounds decompose after 300 degrees C and both forms of this macrocycle, contain four hydration water molecules. The main decomposition products are H2O, CO2, NH3 and isocyanic acid as we could detect by FTIR spectroscopy. Finally, we verified that the caviplex loses its chloride ion after 270 degrees C and may produce the anion-free macrocyle upon heating.
Keywords: Methyl-bambus[6]uril; Thermal behaviour; Macrocycle; Caviplex